(3eMGSHI GdafGOb, eMGSHI GdeWGYe, GdJMdjd GdeGdj hGdEMUGFjs - (3QVhGf MdhI(B, (3MfGfs ((3YeGf(B;(3OGQ GdKbGaI ddfTQ hGdJhRjY(B:s (3GdOGQ GdYdejI GdOhdjI ddfTQ hGdJhRjY(B,s, 2001)
(3eMGSHI GdafGOb heMGSHI GdeWGYe(B: (3GdfTGW GdafObj h NUGFUg, GdJfXje GdeMGSHj h GdJfXje GdGOGQj, Odjd GdMSGHGJ(B- (3GdGWGQ GdYGe ddfXGe GdGeQjcj dMSGHGJ GdafGOb, bGFeI GdeQcR GdeGdj(B- (3MSGHGJ GdGUhd h GdGdJRGeGJ h Mbhb GdedcjI , GSGSjGJ eMGSHI GdGjQGOGJ , eMGSHI GdGjQGOGJ h OhQJgG (B'' (3GdeSJfOjI (B- (3GdeMGSHjI (B- (3GjQGOGJ bSe GdZQa, bGFeI ONd bSe GdZQa, eMGSHI GdGjQGOGJ h OhQJgG GdeSJfOjI (B- (3GjQGOGJ bSe GdGZPjI h GdeTQhHGJ, eMGSHI JcdaI bSe GdGZPjI h GdeTQhHGJ, bGFeI ONd bSe GdGZPjI h GdeTQhYGJ, GdGbSGe GdGjQGOjI GdGNQi, GdQbGHI Ydi GdGjQGOGJ aj GdGbSGe GdGjQGOjI h eQGLYJgG, CbSGe eMGSHjI CSGSjI , eMGSHI GdQhGJH h GdGLhQ, GdSLdGJ h GdOaGJQ GdeMGSHjI, GdSLdGJ h GdOaGJQ GdeMGSHjI GdafObjI hab GdWQjbI GdGfLdjRjI , OaJQ GdGSJGP GdYGe h OaGJQ GdGSJGP GdeSGYOI, CeKdI TGedI deMGSHI GdeWGYe hab GdfXGe GdGeQjcj deMGSHI GdafGOb h GdeWGYe eY JWHjbGJ ddMd , eKGd TGed eJcGed dGYOGO GdbhGFe GdeGdjI aj GdfTGW GdafObj GdcHjQ GdMLe, JWHjbGJ ddMd Mhd GdfTGW GdafObj GdcHjQ GdMLe(B/- (3GdJMdjd GdeGdj hGdGMUGFj(B: (3GdJMdjd GdeGdj, GdfSH GdGMUGFjI GdafObjI (B.s
Keywords: (3GdJMdjd GdeGdjs; (3GdafGOb(B-(3eMGSHIs; (3GdeMGSHI GdJMdjdjIs